MEMBRAN SELULOSA ASETAT DARI NATA DE BAMBOO SEBAGAI MEMBRAN MIKROFILTRASI - Fikka Kartika Widyastuti; Fenny Suryanti (Universitas Tribhuwana Tunggadewi Malang, 2018)
Research has been conducted in order to utilize bacterial cellulose or nata as an alternative source of cellulose from plants for the manufacture of cellulose acetate which is applied as microfiltration membrane. Nata de bamboo is made from fermented bamboo shoots with the help of Acetobacter xylinium bacteria. Nata de bamboo is pressed with a hydraulic press tool then dried and then used as a base material of cellulose acetate membrane. The method used in the manufacture of cellulose acetate membranes is a common method that includes the swelling stage using glacial acetic acid, activation, acetylation and hydrolysis. The result of hydrolysis is then printed on a glass plate with immersion precipitation method to produce cellulose acetate membrane. Membrane characterization in the form of membrane permeability testing and membrane selectivity. Membrane permeability reached the value of flux of 140 L.m-2.jam-1 and membrane selectivity test yielded rejection coefficient of 90%. From this result it is concluded that cellular nitrate based acetate membrane can be used as microfiltration membrane.